2017
DOI: 10.1038/ncomms14573
|View full text |Cite
|
Sign up to set email alerts
|

RD26 mediates crosstalk between drought and brassinosteroid signalling pathways

Abstract: Brassinosteroids (BRs) regulate plant growth and stress responses via the BES1/BZR1 family of transcription factors, which regulate the expression of thousands of downstream genes. BRs are involved in the response to drought, however the mechanistic understanding of interactions between BR signalling and drought response remains to be established. Here we show that transcription factor RD26 mediates crosstalk between drought and BR signalling. When overexpressed, BES1 target gene RD26 can inhibit BR-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
205
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(223 citation statements)
references
References 71 publications
5
205
0
1
Order By: Relevance
“…However, transcript induction of other genes (such as SlRD29B, SlAOX1a, SlAOX2, SlSDR1C, SlDREB2A1 and SlDREB2A2) by SlTAF1 required salt, suggesting an involvement of a yet unknown salt activated factor(s) in the regulation of those genes by SlTAF1. RD26 was reported to regulate salt and drought stress Li et al, 2014;Ye et al, 2017). For example, JUB1 appears to enhance the tolerance towards drought and salt stress in part via an accumulation of proline in Arabidopsis, banana and tomato (A.…”
Section: Researchmentioning
confidence: 99%
“…However, transcript induction of other genes (such as SlRD29B, SlAOX1a, SlAOX2, SlSDR1C, SlDREB2A1 and SlDREB2A2) by SlTAF1 required salt, suggesting an involvement of a yet unknown salt activated factor(s) in the regulation of those genes by SlTAF1. RD26 was reported to regulate salt and drought stress Li et al, 2014;Ye et al, 2017). For example, JUB1 appears to enhance the tolerance towards drought and salt stress in part via an accumulation of proline in Arabidopsis, banana and tomato (A.…”
Section: Researchmentioning
confidence: 99%
“…RD26, a member of the ATAF subfamily of TFs in A. thaliana (Jensen et al ., ), has previously been identified as a positive regulator of developmental and dark‐induced senescence (Li et al ., ) and jasmonic acid‐induced Chl degradation (Zhu et al ., ), while it is also involved in abiotic and biotic stress signaling (Fujita et al ., ; Tran et al ., ; Zheng et al ., ; Ye et al ., ). Here, we report RD26 as an important regulator of metabolic reprogramming during senescence by controlling the expression of genes across the entire spectrum of the cellular degradation hierarchy.…”
Section: Introductionmentioning
confidence: 97%
“…This approach enables various comparative physiological analyses (Salvi et al ). Interestingly, recent reports indicate that reduction of BR responses improves plant tolerance to drought (Feng et al , Northey et al , Ye et al ). Our recent results also indicated that under drought conditions the semi‐dwarf NILs exhibit delayed wilting when compared with a wild‐type cultivar (Gruszka et al ).…”
Section: Introductionmentioning
confidence: 99%